Analysis of the Meaning of Hadith About Destiny in Abdullah Gymnastiar's Instagram Posts - Bakar, Abu; Manik, Zulfirman (Sekolah Tinggi Agama Islam Sumatera Medan, 2025)
Abdullah Gymnastiar is one of Indonesia's most popular preachers who has been able to utilize social media to convey religious messages in a calm, simple, and relevant manner. Through his Instagram account, Abdullah Gymnastiar discusses various Islamic topics, including theological concepts such as destiny, which often cause confusion among the general public. In this context, it is important to examine how the meaning of hadiths about destiny is communicated in a modern and easily understandable way. This study aims to analyze the meaning of hadiths about destiny conveyed by Abdullah Gymnastiar through Instagram. The research was conducted using content analysis and a qualitative approach, specifically interpretive analysis. The research data was collected from posts, captions, videos, and comments on Abdullah Gymnastiar's Instagram account. The results of the study indicate that Abdullah Gymnastiar interprets hadiths about destiny by emphasizing the balance between human effort and tawakal (trust in God's will). This message is framed as spiritual motivation that encourages the community to continue striving. The implication is that contemporary preachers need to be creative in utilizing digital media so that religious messages can be conveyed in a communicative, inspiring, and easily understandable manner to the public.